2017
DOI: 10.1177/1071100717732383
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Results of a Ruptured Deltoid Ligament Repair During an Acute Ankle Fracture Fixation

Abstract: Level III, retrospective comparative case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 41 publications
0
80
0
2
Order By: Relevance
“…Zhao et al [17] reported a significantly small MCS in the DL repair group postoperatively and at final follow-up (P = 0.03). Woo et al [16] reported a significant difference in the average final follow-up for MCS between the two groups (p = 0.001), but there was no difference seen in the immediate postoperative average MCS. Gu et al [15] found a significant reduction in the MCS between preoperative and postoperative radiographs in both groups at 1 year follow-up, with a greater improvement in the DL repair group (P = 0.02).…”
Section: Medial Clear Spacementioning
confidence: 96%
See 2 more Smart Citations
“…Zhao et al [17] reported a significantly small MCS in the DL repair group postoperatively and at final follow-up (P = 0.03). Woo et al [16] reported a significant difference in the average final follow-up for MCS between the two groups (p = 0.001), but there was no difference seen in the immediate postoperative average MCS. Gu et al [15] found a significant reduction in the MCS between preoperative and postoperative radiographs in both groups at 1 year follow-up, with a greater improvement in the DL repair group (P = 0.02).…”
Section: Medial Clear Spacementioning
confidence: 96%
“…The AOFAS score was reported in all included studies. Gu et al [15] reported significantly better AOFAS scores after DL repair (P = 0.001); yet, in the two studies by Woo et al [16] and Zhao et al [17], the AOFAS scores were comparable in the two groups, with no statistical significance (P > 0.05).…”
Section: Functional Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that detecting and repairing deltoid ligament injury produces better results in ankle fractures with syndesmotic instability. 52,53 Finally, the number of patients included in this study was small, limiting the generalizability of the results. The small sample size also increases the difficulty of comparing the radiographic and clinical results according to the specific fracture type.…”
Section: Discussionmentioning
confidence: 98%
“…Estudos recentes sugerem que a reconstrução do LD promove recuperação funcional, alivia a dor e diminui o espaço livre medial (ELM). Outros estudos comparam tratamento conservador, reparo do LD e tratamento cirúrgico com ou sem reparo do LD (6)(7)(8)(9)(10)(11) .…”
Section: Introductionunclassified